Synthesis and characterization of thermally stable zirconia based mesoporous nanosilica with metalloporphyrin encapsulation - Nadeem, S.; Iqbal, F.; Mutalib, M.I.A.; Abdullah, B.; Shaharun, M.S. (American Institute of Physics Inc., 2017)
Metal composite materials-48 (MCM-48) with silica zirconia mesoporous matrix (having a Zr/Si ratio of 0.02) has been developed successfully using autogenous conditions and Copper tetra phenyl porphyrin (CuTPP) inclusion via flexible ligand approach. Thermo gravimetric analysis (TGA) was used to study the thermal stability which gives the stability up to 700°C, Fourier transform infrared spectroscopy (FTIR) for the functional group attachment also confirmed the MCM-48 structure and the Zirconia addition and X-Ray photon spectroscopy (XPS) for the binding energies and bonding also revealed the surface Zr4+ states. DRS-UV-Vis study for the photophysical behaviour, visible light activation and band gap reduction which reduced from 5.6 to 2.8 eV. All the characterizations have confirmed that nanoscale mesoporous silica with successful inclusion of zirconia in the matrix and the encapsulation of CuTPP was confirmed via diffuse reflectance (DR Uv-Vis) spectroscopy. © 2017 Author(s).